Distribusi Herpetofauna di Kawasan Hutan Lindung Gambut Sungai Buluh Tanjung Jabung Timur - Anggit Prima Nugraha; Dawam Suprayogi; Winda Dwi Kartika; Andri Setiawan (Fakultas Biologi | Universitas Jenderal Soedirman, 2021)
Hutan Lindung Gambut (HLG) Sungai Buluh is one of the village forests in East Tanjung Jabung. Peat soil has high water content and is herpetofauna habitat. Herpetofauna acts as a prey and predator in the peat ecosystem. Some of them occupy the position of top predators on food networks in the peat ecosystem. The existence of this group of animals also acts as an environmental bioindicator which can be indicated by its species richness and individual count. This research was conducted on two habitat conditions (terrestrial and aquatic) with the aim of this study were the distribution and habitat characteristics of herpetofauna in the HLG Sungai Buluh. This study used the Visual Encounter Survey (VES) method which was combined by transect lines in each habitat. Sampling was done nocturnal and diurnal. The specimens obtained then preserved in 70% alcohol. The results showed total of 105 individual herpetofauna consisting of 4 Anura families (Bufonidae 1 species, Dicroglossidae 3 species, Rhacophoridae 3 species, and Ranidae 4 species) and 4 Reptile families (Agamidae 3 species, Scincidae 2 species, Gekkonidae 1 species, and Natricidae 1 species). Eleven species were found in the terrestrial habitat transect while eleven species were found in aquatic habitat transects. Furthermore, four species were found in both habitat transects. From these results it can be concluded that the HLG Sungai Buluh has a suitable habitat for herpetofauna. However, further research needs to be carried out covering the entire are of HLG Sungai Buluh